Evaluasi Penerapan Metode Al-Husna dengan Goal Oriented Evaluation Model di Paud Tahfidzul Qur’an Yurefi Kendari - Nur Zakiyah Safitri; Nurlathifah Thulfitrah B. (Karakter : Jurnal Riset Ilmu Pendidikan Islam, 2026)
This research is motivated by the high rate of inability to read the Quran in Indonesia and the urgency of providing appropriate learning stimuli during the golden period of child development. The Al-Husna method was chosen because it emphasizes the principles of simplicity, ease, and tartil, which are considered relevant to the characteristics of early childhood. This study aims to assess the effectiveness of the application of the Al-Husna method in Quran learning at PAUD Tahfidzul Qur'an Yurefi Kendari using the Goal-Oriented Evaluation Model. The research method used is descriptive qualitative, with data collection techniques including observation, interviews, and documentation studies. The evaluation results show that the application of the Al-Husna method has met the learning objectives that have been set at PAUD Tahfidzul Qur'an Yurefi. These achievements include improving students' abilities in recognizing and pronouncing hijaiyah letters with the support of visual codes, mastery of syllables of hijaiyah letters, and understanding the punctuation system using standards according to Rasm Uthmani, achieving efficiency in the use of time and materials in the learning process, and creating a fun, active, and participatory learning environment for children. The identified challenges primarily relate to the need for educators to have a comprehensive understanding of the Al-Husna method. However, schools can address these challenges by implementing ongoing training and mentoring programs. Overall, the findings of this study indicate that the Al-Husna method is effective in building a foundation of basic Quranic reading skills and understanding in early childhood, using a child-friendly and meaningful approach. Therefore, this method can be used as a strategic alternative for teaching Quranic reading and understanding in educational institutions.